Revision of freshwater shrimps belonging to Caridina weberi complex (Crustacea: Decapoda: Atyidae) from Polynesia with discussion on their biogeography. Issue 13 (11th April 2019) - de Mazancourt, Valentin; Marquet, Gérard; Keith, Philippe
ABSTRACT: Caridina weberi, an emblematic species of the ' C. weberi complex', was described by De Man in 1892 from different localities in Indonesia. Until now, this species was thought to have a wide distribution in Polynesia. Numerous specimens identified as C. weberi were collected recently from various Polynesian islands. In the context of integrative taxonomy, they were morphologically and genetically studied. Three new species allied to C. weberi are here described: C. marquesensis n. sp., C. futunensis n. sp. and C. tupaia n. sp. The occurrence of C. rapaensis, another species part of the ' C. weberi ' complex is confirmed. Descriptions or redescription of these species are given as well as their geographical and ecological distributions. The position of these species in the complex is clarified. A key is provided to facilitate identification. www.zoobank.org/urn:lsid:zoobank.org:pub:17B62044-4D99-48EE-A665-3E5E7F1A864B